A Research Strategy Case Study of Alcohol and Drug Prevention by Non-Governmental Organizations in Sweden 2003-2009 - Larsson Madelene; Geidne Susanna; Eriksson Charli; Pettersson Camilla (BMC, 2011)
Abstract Background Alcohol and drug prevention is high on the public health agenda in many countries. An increasing trend is the call for evidence-based practice. In Sweden in 2002 an innovative project portfolio including an integrated research and competence-building strategy for non-governmental organisations (NGOs) was designed by the National Board of Health and Welfare (NBHW). This research strategy case study is based on this initiative. Methods The embedded case study includes 135 projects in 69 organisations and 14 in-depth process or effect studies. The data in the case study has been compiled using multiple methods - administrative data; interviews and questionnaires to project leaders; focus group discussions and seminars; direct and participatory observations, interviews, and documentation of implementation; consultations with the NBHW and the NGOs; and a literature review. Annual reports have been submitted each year and three bi-national conferences Reflections on preventions have been held. Results A broad range of organisations have been included in the NBHW project portfolio. A minority of the project were run by Alcohol or drug organisations, while a majority has children or adolescents as target groups. In order to develop a trustful partnership between practitioners, national agencies and researchers a series of measures were developed and implemented: meeting with project leaders, project dialogues and consultations, competence strengthening, support to documentation, in-depth studies and national conferences. A common element was that the projects were program-driven and not research-driven interventions. The role of researchers-as-technical advisors was suitable for the fostering of a trustful partnership for research and development. The independence of the NGOs was regarded as important for the momentum in the project implementation. The research strategy also includes elements of participatory research. Conclusions This research strategy case study shows that it is possible to integrate research into alcohol and drug prevention programs run by NGOs, and thereby contribute to a more evidence-based practice. A core element is developing a trustful partnership between the researchers and the organisations. Moreover, the funding agency must acknowledge the importance of knowledge development and allocating resources to research groups that is capable of cooperating with practitioners and NGOs.